KONFIGURASI KARAWITAN JAWATIMURAN - Aris Setiawan (Gelar : Jurnal Seni Budaya, 2013)
Jawatimuran karawitan/ east Java musicians during its development become into a sub dominantwhen compared with Surakarta or Yogyakarta. Jawatimuran said often as a complement to thewriting of that two major genres of the musical. As a result, many ordinary people who think KarawitanJawatimuran is not somewhat different with style from Surakarta and Yogyakarta . This article triesto use descriptive analysis, ie, classifying data related to the uniqueness Karawitan Jawatimuranthen assembled , analyzed, presented in a coherent and deeply. Thus ,to bring back its configuration(appearance of ) musical Jawatimuran not merely re- describe, but as an attempt to make senseof today’s its appearance increasingly not find space discourse. The result can be seen thatJawatimuran musicians have different specifications, namely forms, techniques, terminologyand so forth.